2021
DOI: 10.33317/ssurj.314
|View full text |Cite
|
Sign up to set email alerts
|

Q-switched EDF LASER Cavity using ITO as Saturable Absorber

Abstract: In this work, we have experimentally reported Q-switched pulse generation by indium tin oxide as a saturable absorber. First the glass slide was placed in electron beam deposition chamber and indium tin oxide layer was coated over the glass slide. Then the indium tin oxide was exfoliated from the glass slide, over the fiber ferrules in erbium doped fiber laser cavity. The Q-switched laser operated at center wavelength of 1562.6 nm. The repetition rate and pulse width were obtained to be 48.31-64.52 kHz and 5.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…also demonstrated the application of ITO in Q‐switched EDFL with the pulse duration of 4.23 μ$\umu$s at 1562.6 nm. [ 270 ] Moreover, MgO and PbO are also demonstrated as SAs in ultrafast photonics with great experimental results, which have advantages of low cost and high stability. In 2019, Khaleel et al.…”
Section: Applications Of Nanomaterials In Ultrafast Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…also demonstrated the application of ITO in Q‐switched EDFL with the pulse duration of 4.23 μ$\umu$s at 1562.6 nm. [ 270 ] Moreover, MgO and PbO are also demonstrated as SAs in ultrafast photonics with great experimental results, which have advantages of low cost and high stability. In 2019, Khaleel et al.…”
Section: Applications Of Nanomaterials In Ultrafast Lasersmentioning
confidence: 99%
“…Recently, Nizamani et al also demonstrated the application of ITO in Q-switched EDFL with the pulse duration of 4.23 μs at 1562.6 nm. [270] Moreover, MgO and PbO are also demonstrated as SAs in ultrafast photonics with great experimental results, which have advantages of low cost and high stability. In 2019, Khaleel et al proposed a fiber laser enabled by MgO served as SAs, where 5.6-ps mode-locked pulses with SNR of 50 dB were observed.…”
Section: Metal Oxidesmentioning
confidence: 99%